Improving Science Learning Outcomes and Critical Thinking through Problem-Based Learning in Elementary Education - Meggi Rahayu; Wisman Wisman; Selvina Doranggi; Andi Salahuddin (CV. Dharma Samakta Edukhatulistiwa, 2026)
Low science learning outcomes and limited critical thinking skills among elementary school students remain a significant challenge in science education, particularly due to the use of less interactive instructional approaches. This study investigates the effect of the Problem-Based Learning (PBL) model on students’ science learning outcomes and critical thinking skills among fifth-grade students at SD Inpres 3 Tatura. This study employed a quasi-experimental design using a pretest–posttest control group approach. The sample consisted of 53 students selected through total sampling, with one class assigned as the experimental group and the other as the control group. Data were collected using essay-based tests designed to measure students’ learning outcomes and critical thinking skills, and were analyzed using an independent sample t-test. The results indicate that students who were taught using the PBL model achieved significantly higher learning outcomes and demonstrated improved critical thinking skills compared to those who received conventional instruction (p < 0.05). The improvement was evident in students’ ability to analyze problems, construct arguments, and evaluate solutions. These findings suggest that Problem-Based Learning is an effective instructional strategy for enhancing both science learning outcomes and critical thinking skills, and can be considered a practical approach for improving elementary science education.